An Introduction to the Music of Milton Babbitt - Mead, Andrew Washburn (Book collections on Project MUSE., 2014)
In this celebration of Milton Babbitt's art, Andrew Mead explores the development of a central figure in contemporary American music. As a teacher and writer, Babbitt has influenced two generations of students, including such notable musicians as Stephen Sondheim and Donald Martino. He has helped establish the study of music theory as a serious academic pursuit, and his articles on Schoenberg, Stravinsky, and the twelve-tone system constitute a seminal body of research. But Babbitt is first and last a composer, whose works are, in Mead's words, ""truly music to be heard."" With Mead as a gu